Laboratory observations of slow earthquakes and the spectrum of tectonic fault slip modes - J. R. Leeman; D. M. Saffer; M. M. Scuderi; C. Marone (Nature Communications, 2016)
Slow earthquakes, where fault slip is slow, can be large and may help trigger regular earthquakes, but the mechanics of slow slip are not fully understood. Leeman et al.show through laboratory experiments that slow slip behaviour on faults is controlled by the frictional dynamics of the surrounding material.